Internal Control System Applied To Online Based Company Accounting Information Systems - Endah Prawesti Ningrum; Resista Vikaliana; Susan Rachmawati; Nurzalinar Joesah; Arman Syah Putra; Nurul Aisyah (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
In a company, many systems are made to help the company run better, one of which is an accounting information system. In this study, the author raises the issue of how to create an online system that can be controlled remotely by company leaders in order to know the current state of the company. The method used in this study is a method by carrying out 4 stages, namely, the first stage is the boundary stage, the second is the input stage and the third is the process stage and the fourth is the output stage with these four steps, which are certain steps that will clearly be carried out in order to answer the problem existing research. The problem raised in this research is how to create a system that can be monitored remotely. Because there are many shortcomings of the existing system in the current system. Therefore, making an online system is one solution that is made in order to be able to monitor a company remotely. This study aims to make it easier for company leaders to monitor companies online because there are many problems if they are not monitored regularly with this online system, the company can be assisted in thinking online by company leaders.